Transport operations as a part of supply chain management based on the Quick Response method - Branská, Lenka (Univerzita Pardubice, 2008)
Companies' tendency to base the competitive advantage on speed and flexibility of satisfying the customers' needs lead to inter-company linkage of material flows and establishing of supply chains. To increase their efficiency, it is then possible to realize supply chain management on the basis of the Quick Response method. This shall allow radical increase of the value provided to the customers, and that is without automatic pressure on cost increase. QR-based realization of supplies undoubtedly requires adjusting of the primary processes which directly participate in providing the value (sale, production and purchase). It is, however, necessary to adjust also other processes, i.e. those that support the value-creating process. One of the processes the efficiency of which pivotally affects successfulness of the value-creating process is transport. Application of the QR method invokes changes in realization of transport operations under own company transport but it may also significantly affect the way of business relations setting with transport intermediaries (as agent, broker) or, as the case may be, with the independent forwarding companies themselves. Their involvement in the QR-based supply chain management must, however, be such that it would make the value increase not only for the company but to the both partners. The article describes impacts of the Quick Response method application in the company in realization of transport operations.
Dopravní operace jako součást řízení hmotných toků na bázi metody Quick Response
Verkehrsoperationen als der Bestandteil der Materialflusslenkung auf der Basis der Quick-Response Methode